Earthquake fault-induced surface rupture A hybrid strong ground motion simulation technique and discussion for structural design. - Tahghighi, Hossein (Earthquake engineering & structural dynamics.)
Unique to the near-source region of a large earthquake is the occurrence of strong impulsive ground motion and surface faulting referred to as ?fling-step? motion. The objective of this study is to synthesize broad-band time histories over a wide range of frequencies by characterizing rupture directivity and fling effects from the comprehensive strong motion database of the near-fault Chi-Chi event. To aid in the generation of these special types of ground motions, a hybrid modeling technique is introduced based on the stochastic finite-fault radiation method and an efficient analytical approach to incorporate the observed low-frequency features in the records close to the ruptured fault. The results show that the overall agreement among the developed hybrid methodology and recorded waveforms and response spectra is quite satisfying. A brief discussion on the design of infrastructures near seismic fault is also included.